Everything you need to know about teen marriage - Ayer, Eleanor H. (New York Rosen Pub. Group, 1990)
Examines the choices involved in teenage marriage, as well as the joys, problems, expectations, and implications. Presents case studies for and against teenage marriage.
Includes bibliographical references (p. 62-63) and index.
Keywords: Teenage marriage -- United States -- Juvenile literature; Marriage